The Aleksander Kwasniewski’s Polish Diplomatic Breakthrough to the EU and NATO (Natalia Buglay’s «Kwasniewski’s Epoque in Polish foreign policy (1995–2005)» review) 181-189 - Andriy Martynov; Hanna Harlan (Європейські історичні студії, 2018)
The monograph delivers a complex study of shaping the foreign policy strategy and of implementing the priorities of the foreign policy of the Republic of Poland in 1995-2005. Through utilizing a wide and diverse source material and large amount of literature, the conceptual and historical basis, the regulatory and institutional framework of the foreign policy of Poland have been investigated. Particular attention is paid to the complex implementation process of the key tasks of the foreign policy of the Republic of Poland related to its accession to the North Atlantic Alliance and the European Union. According to the research materials, the successful Euro-Atlantic and European integration of the Republic of Poland managed top have strengthened the position thereof on the international arena and brought peace and security to Poland. What is more, the integration has led to democratic changes in the legislative sphere, has increased its macroeconomic stability and has improved the situation in the social sphere. Special attention is paid to the East direction of the foreign policy of the Republic of Poland. In particular, the patterns and stages of the development of good neighborly relations with Ukraine have been underlined, for the latter had reached the level of strategic partnership in the investigated period. The formation of stable relations with Belarus, Lithuania and the Russian Federation has been outlined as well. The role, the problems and the prospects of the cross-border cooperation and activities of the European regions to deepen and improve their cooperation have been examined individually.